Nilai-Nilai Pendidikan Islam Dalam Spiritual Company Dan Implikasinya Terhadap Perilaku Keagamaan Karyawan Waroeng Steak And Shake Surabaya - khalim, Ainul; Layaliya, Nuwairotul (Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to examine the application of Islamic educational values in the Waroeng Steak and Shake Surabaya company which is based on a spiritual company. With a qualitative approach, data is collected through observation, in-depth interviews, and documentation. The results of the study show that the concept of spiritual company is in line with Islamic teachings, aiming to motivate employees to work based on the Qur'an, sunnah, and conscience. The Islamic educational values applied include the values of aqidah, worship, and morals. The implications of applying these values can be seen in employee behavior, such as tawaduk, honest, friendly, increased prayer and reading the Qur'an, love of almsgiving, respect for time, and enthusiasm for work. This research confirms that Islamic education can be applied effectively in the company environment to build an Islamic work culture.